A common physical and control interface for ISAM operations - Martin, Jack; Sahu, Sripad; Zaidi, Yaseen (https://www.isamconference.co.uk/event/bfa7fc93-540d-44b8-be40-4216790688ec/home, 2025)
The Common Physical and Control Interface (CPCI) is a standardised, open-source solution to enhance interoperability in In-Orbit Servicing, Assembly, and Manufacturing (ISAM) operations. The absence of a universal interface in current space systems increases integration complexity, costs, and inefficiencies. CPCI leverages IEEE 802.3 Power over Ethernet (PoE) to enable simultaneous power and data exchange, providing a scalable and modular plug-and-play solution for future space missions.